In Dante's Wake : Reading from Medieval to Modern in the Augustinian Tradition - Freccero, John (Book collections on Project MUSE., 2015)
"In Dante's Wake presents a collection of essays from internationally renowned Dante scholar John Freccero. Penetrating first the Divine Comedy and then the powerful influence of Dante on those who followed him, Freccero's volume is an invaluable companion for any reader of Dante"--